2011
DOI: 10.1038/ijo.2011.7
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and postnatal programming of body composition in obese children and adolescents: evidence from anthropometry, DXA and the 4-component model

Abstract: Background: Low-birth weight has been proposed to programme central adiposity in childhood. However, there is little information on associations between fetal weight gain and fat distribution within obese individuals. Objectives: To investigate associations between birth weight and postnatal weight gain with body composition in a sample of obese children and adolescents. Subjects and methods: Body composition was measured using anthropometry, dual-emission X-ray absorptiometry and the 4-component model in 45 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 39 publications
0
14
1
Order By: Relevance
“…Both a high maternal BMI [7,9] and a high GWG [17,18] have been recognized as significant and independent predictors of future child and adult obesity [61,62,63,64]. While the association between maternal and infant and childhood adiposity is likely to reflect a combination of shared genetic and environmental factors in addition to in utero programming pathways, the latter may be modifiable and therefore of enormous significance as a strategy to prevent or limit the early onset of obesity.…”
Section: Tablementioning
confidence: 99%
“…Both a high maternal BMI [7,9] and a high GWG [17,18] have been recognized as significant and independent predictors of future child and adult obesity [61,62,63,64]. While the association between maternal and infant and childhood adiposity is likely to reflect a combination of shared genetic and environmental factors in addition to in utero programming pathways, the latter may be modifiable and therefore of enormous significance as a strategy to prevent or limit the early onset of obesity.…”
Section: Tablementioning
confidence: 99%
“…The relative contribution of in utero and postnatal environment to childhood metabolism and long-term risk of obesity is currently unclear. Eriksson et al 20 found body fat was not correlated in infants at 1 and 12 weeks of age, and Wells et al 40 found that postnatal weight gain had a stronger influence than fetal weight gain on fat distribution. Neither study controlled for maternal GDM status.…”
Section: Main Findingsmentioning
confidence: 99%
“…Growth and development in early life is strongly associated with life-long health, and adverse influences can persist and manifest later in life (6)(7)(8). In the study of bone densitometry, most disorders associated with increased fracture risks, as identified by the International Society for Clinical Densitometry, manifest in infancy, if not in utero (32).…”
Section: Anthropomorphic Infant Dxa Phantommentioning
confidence: 99%
“…Because early growth affects health later in life, early testing and monitoring may be wise in certain cases (6)(7)(8). One may apply similar logic to the current obesity epidemic, where early intervention may be needed to moderate future health issues (9).…”
mentioning
confidence: 99%